Disentangling the conductivity spectra of two-dimensional organic conductors - Dressel, M.; Faltermeier, D.; Dumm, M.; Drichko, N.; Petrov, B.; Semkin, V.; Vlasova, R.; Méziere, C.; Batail, P. (Physica. B, Condensed matter, 2009)
The optical spectrum of a κ-phase organic conductor is thoroughly analyzed for the example of κ-(BEDT-TTF)2Cu[N(CN)2]Br0.85Cl0.15 in order to identify its various contributions. It is shown how the complex spectra can be decomposed using different approaches; the intradimer and interdimer contributions are discussed. In particular the fingerprints of electronic correlations in these spectra are considered.